PENGARUH MOTIVASI, KEPEMIMPINAN, KEPUASAN KERJA, DAN PEMBERDAYAAN GURU TERHADAP KINERJA GURU TK PADA GUGUS V KECAMATAN SEMAMPIR SURABAYA - NITAWATI ELLY YUNIAR (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2018)
This study has the main objective is to know and prove partially the influence of motivation on the performance of Kindergarten Teachers in Cluster V Semampir Subdistrict, the influence of leadership on the performance of Kindergarten Teachers in Cluster V Semampir Subdistrict, the influence of job satisfaction on the Kindergarten Teacher's performance in Cluster V Semampir District, Teacher empowerment to the performance of Kindergarten Teachers in Semampir Subdistrict V, and to know and prove simultaneously the influence of motivation, leadership, job satisfaction and empowerment of Teachers on the performance of Kindergarten Teachers in Semampir V Cluster V, and to know and prove which of the variables motivation, leadership job satisfaction and empowerment of Teachers who have a dominant influence on the performance of Kindergarten Teachers in Cluster V Semampir District. The variables in this study consist of three independent variables, namely Motivation (X¬1), Leadership (X2), Satisfaction (X3) and Empowerment (X4), and one dependent variable is Performance Improvement (Y). From the results of research found The first hypothesis proposed in this study is true this means that the value of t arithmetic for each independent variable is greater than the value of t table. Thus Ho is rejected and Ha accepted means independent variables that include motivation (X1), leadership (X2), job satisfaction (X3) and Empowerment (X4) in partial / own significant influence on the performance variables Teacher TK (Y) in Cluster V Semampir District. The second hypothesis proposed in this study is true because the value of F arithmetic is greater than the value of F table. Thus Ho is rejected and Ha accepted, meaning free variables which include motivation (X1), leadership (X2), job satisfaction (X3) and Empowerment (X4) simultaneously / significant effect on teacher performance variable TK (Y) in Cluster V Subdistrict Semampir. Leadership Variable (X2) is the independent variable that predominantly affects the dependent variable that is Teacher TK (Y) performance in Cluster V Semampir District.